Improving Young Riders’ Situational Awareness Through Driving Simulation: A University-Based Study in Indonesia - Shulima, Attalarik; Susanti, Lusi; Zadry, Hilma Raimona; Huda, Ashila Nurul (invotek, 2025)
Motorcycle-related crash remain a major concern among university students in Indonesia. This study investigates situational awareness (SA) among novice motorcyclists at Universitas Andalas (UNAND) and evaluates the effectiveness of a simulation-based training intervention. Using the QUASA (Quantitative Analysis of Situational Awareness) method, baseline and post-training assessments were conducted to measure SA accuracy. The simulation module, developed using Unreal Engine and AI-assisted audio feedback, presented realistic traffic scenarios designed to enhance cognitive engagement. Findings indicate a substantial improvement in SA, with actual awareness scores increasing by approximately 30 percentage points post-intervention. Perceived accuracy also showed measurable gains. Despite a small simulation sample, results suggest that immersive training improves hazard perception and rider decision-making. These outcomes emphasize the value of technology-enhanced learning in addressing safety risks among young riders. Further research with control groups and larger samples is needed to generalize findings. Ethics clearance, data availability, and conflict of interest disclosures have been included.